Cloning, expression, crystallization and preliminary structural studies of dihydrodipicolinate reductase from Acinetobacter baumannii. Issue 6 (31st May 2013) - Kaushik, Sanket; Singh, Avinash; Sinha, Mau; Kaur, Punit; Sharma, Sujata; Singh, Tej P.
<x xml:space="preserve">Abstract</x> Acinetobacter baumannii is a virulent pathogenic bacterium that is resistant to most currently available antibiotics. Therefore, the design of drugs for the treatment of infections caused by A. baumannii is urgently required. Dihydrodipicolinate reductase (DHDPR) is an important enzyme which is involved in the biosynthetic pathway that leads to the production of L‐lysine in bacteria. In order to design potent inhibitors against this enzyme, its detailed three‐dimensional structure is required. DHDPR from A. baumannii (AbDHDPR) has been cloned, expressed, purified and crystallized. Here, the preliminary X‐ray crystallographic data of AbDHDPR are reported. The crystals were grown using the hanging‐drop vapour‐diffusion method with PEG 3350 as the precipitating agent The crystals belonged to the orthorhombic space group P222, with unit‐cell parameters a = 80.0, b = 100.8, c = 147.6 Å, and contained four molecules in the asymmetric unit. The complete structure determination of AbDHDPR is in progress.